Association of Plastic Surgeons of India Postgraduate Medical Education (APSI-PGME) Course: How Far Have We Reached? - Veena Kumari Singh; Ankur Bhatnagar; Ravi Mahajan; Vijay Kumar; Nitin Mokal; Hari Venkatramani (Indian Journal of Plastic Surgery)
Background The Association of Plastic Surgeons of India (APSI) felt the need to create an opportunity for the residents to participate in a mock viva voce patterned course on the national platform in front of examiners from the various centers and instill a feeling of confidence and healthy competition among them. Apart from the responsibilities of teaching departments running the formal plastic surgery training programs, the association also took upon itself to further strengthen the academics, especially of residents working at centers that lack regular teaching classes, and started the postgraduate medical education course in October 2022.